ANALISIS KELAYAKAN USAHATANI CABAI MERAH DI LAHAN GAMBUT KOTA PALANGKA RAYA KALIMANTAN TENGAH (The Feasibility Of Red Chili Farming In Peatlands Of Palangka Raya In Central Kalimantan) - A., astri (Universitas Palangka Raya, 2017)
ABSTRACTRed chili becomes one of commodity contributor to inflation in Central Kalimantan. This is because the price of chili that continues to rise and tend to be unstable, and its supply is still dependent from outside Central Kalimantan.Red chili cultivation has not been developed in peatlands. Palangka Raya has peatland potential for the development of red chilicultivation. The assessment aims to get the feasibility of red chili farming in peatlands of Palangka Raya in Central Kalimantan. The assessment conducted in the PetukKatimpun Villages, District Jekan Raya in June to November 2014, with the planting on the farmerâs land cooperators 0.25 hectares. The technology cultivation adopted from Indonesian Vegetable Research Institute (Balitsa) which has been modified. Pillar varieties used are favored by the market because of its shape. Giving fertilizer used manure 20 t/ha, NPK 16:16:16 1 t/ha, dolomite 2 t/ha, limestone 1 t/ha, calcium boron 14 liter/ha. The assessment results obtained production of red chili 16,743 t/ha. The value of R/C ratio of 5.89 and B/C 4.89 so red chili farming in the peatlands feasible to develop and profitably.Keywords: Red Chili, Peatlands, Feasibility Analysis